Moral distress in nurses - José Ramón Martínez Riera; María Dolores Burguete Ramos; Enrique Saez Alvarez; Carlise Dalla Nora; Rafaela Schaefer; Jorge Lopéz-Gómez; Pablo Rico Berbegal (Universidad de Alicante, 2017)
The aim of this study is to determine the perception of a group of nurses about the causes of mental suffering in their daily work. Method: This is a study using qualitative methodology, obtaining information through a discussion group. The number of attendees was six and worked in different areas. Results: Moral suffering was grouped into three dimensions related to the personal dimension, in relation to the patient and their environment and ultimately to conflicts with the health team. Conclusions: The conceptualization of moral suffering seems complex, as it is clear from the study a large number of existing factors are involved, in relation to the work environment and the private sphere of individuals. About the latter, factors are related to personality, gender, lack of knowledge and commitment to the profession itself that causes pain when the right conditions to practise are not met.